Association between anxiety and sleep quality in periodontally healthy, gingivitis, and periodontitis patients: A cross-sectional study - Abhay P. Kolte; Rajashri Abhay Kolte; Amruta S. Verma; Prachi R. Rathi; Dhanashree Ghoderao (Journal of Indian Society of Periodontology)
Background: There may be a significant link between periodontitis and psychological problems such as anxiety and sleep deprivation because of their complex character. Therefore, this study was conducted to evaluate the association between anxiety, quality of sleep in periodontally healthy, gingivitis, and periodontitis subjects. Materials and Methods: A total of 120 subjects were divided into three groups. Group I: 40 subjects with healthy periodontium; Group II: 40 subjects with gingivitis; Group III: 40 subjects with Stage III or Stage IV periodontitis. Clinically, parameters such as gingival index, plaque index, probing depth, and clinical attachment levels were measured. Zung Self-Rating Anxiety Scale and sleep quality scale (SQS) were used to record anxiety and sleep quality scores, respectively. Results: The anxiety scores obtained in this trial were in the ascending orders with values of 36.02 ± 7.89, 48.15 ± 2.72, and 71.00 ± 0.98 for Group I, Group II, and Group III, respectively, indicating an increasing severity of anxiety levels. On sleep quality assessment, the score for Groups I, II, and III were 17.02 ± 6.26, 24.17 ± 7.53, and 42.12 ± 6.99, respectively, suggestive of disturbances in sleep quality. When compared between the groups, anxiety and sleep quality were found to be associated in an incremental manner from Group I to Group II and from Group II to Group III. Conclusion: There was a positive link between the severity of periodontal disease, anxiety levels, and sleep quality.